Modern Strategies For Managing The Quality Of Personnel In Higher Educational Institutions Of Uzbekistan (Eurasian Journal of Humanities and Social Sciences, 2023)
The article analyzes the experience of higher educational institutions in the field of personnel management, changes in the content and activities of the teaching staff, the introduction of motivational systems based on the rating assessment of the work experience of the teaching staff in the context of new requirements for the effectiveness of higher educational institutions in Uzbekistan . In the course of the study, a proposal was developed on the need to change the system of material incentives for scientific and pedagogical personnel, as well as the introduction of payment “by result” in higher educational institutions.